Mendeteksi Kecurangan Pelaporan Keuangan Dengan Fraud Pentagon Studi Empiris Perusahaan BUMN Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2019-2021 - Mustagfiroh, Handariyatul; Nugroho, Arief Himmawan Dwi (SEIKO : Journal of Management & Business, 2023)
This study aims to examine the effect of Pentagon Fraud on Fraudulent Financial Reporting Detection. The subjects in this study are state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) with a research period of 2019-2021. The sample in this study used a purposive sampling technique with a total of 41 state-owned companies. The analysis technique in this study used Partial Least Square (PLS) with the SmartPLS 4.0.8.7 tool. This study obtained the results that (1) Financial Stability has an effect on the Detection of Fraudulent Financial Reporting, (2) Ineffective Monitoring has no effect on the Detection of Fraudulent Financial Reporting, (3) Change in CEO has an effect on the Detection of Fraudulent Financial Reporting, (4) Frequent Number of CEO's Pictures have no effect on Fraudulent Financial Reporting Detection, (5) Change of Director has effect on Fraudulent Financial Reporting Detection, (6) Change in Auditor has effect on Fraudulent Financial Reporting Detection, (7) External Pressure has effect on Fraudulent Financial Reporting Detection, (8) Nature of Industry has no effect on Detection of Fraudulent Financial Reporting, (9) Financial Target has effect on Detection of Fraudulent Financial Reporting, (10) Total Accrual Ratio has no effect on Detection of Fraudulent Financial Reporting Keywords: Fraud; Fraud Pentagon; Fraudulent Financial Reporting.